2019
DOI: 10.31665/jfb.2019.5174
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine—a natural bioactive dipeptide: bioaccessibility, bioavailability and health benefits

Abstract: Carnosine is a natural dipeptide synthesized by both vertebrate and invertebrate organisms and has functional properties that are specific to muscle and excitable tissues. Recent in vivo and in vitro studies have shown that carnosine presents metal chelating and antioxidant activities and has the ability to inhibit protein carbonylation and glycoxidation. This review describes the health benefits of carnosine in relation to its bioaccessibility, bioavailability and biochemical properties as well as providing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Our understanding of variations in plasma dipeptide levels is still limited but we note that most of the dipeptides assessed in our previous study, albeit not the same ones, were also less abundant in the patient cohort than in the controls. If we focus on the latest literature and ME/CFS patient symptoms, our attention is drawn toward the therapeutic potential of some dipeptides on fatigue, aging, and muscle recovery [41][42][43].…”
Section: Dipeptides Are Decreasedmentioning
confidence: 99%
“…Our understanding of variations in plasma dipeptide levels is still limited but we note that most of the dipeptides assessed in our previous study, albeit not the same ones, were also less abundant in the patient cohort than in the controls. If we focus on the latest literature and ME/CFS patient symptoms, our attention is drawn toward the therapeutic potential of some dipeptides on fatigue, aging, and muscle recovery [41][42][43].…”
Section: Dipeptides Are Decreasedmentioning
confidence: 99%
“…In addition, significant number of investigations of the biochemical and physiological properties of carnosine, including human clinical studies based on carnosine supplement are also available, as reviewed by Boldyrev et al (2013). However, no study is yet available on the advantages and bio-accessibility of dietary carnosine with particular reference to the potential role that it may exert in the GIT itself upon digestion, as reviewed by Xing et al (2019). The authors reported that the release of dietary carnosine from its food matrix would be proportional to its amount in the meat and would depend also on the conditions found in the GIT, including the composition of the food.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, a group of widely distributed histidine-containing dipeptides, including carnosine ( Scheme 3 ), also possess the ability to provide protection against oxidative stress [ 59 , 60 ]. Carnosine ( 6 ) is a well-established chelating molecule, capable of binding transition metals [ 61 ].…”
Section: Intracellular Distribution Of Ironmentioning
confidence: 99%